Impact studies in sport: the development of an assessment process model. Issue 4 (11th May 2020) - O'Reilly, Norm; Abeza, Gashaw; Fodor, Andy; MacIntosh, Eric; Nadeau, John; MacAdam, Lane; Pasqualicchio, Gary; Dottori, Mark; Lawrence, Heather Jane
Abstract : Purpose: The criticisms put forward against economic impact studies lead to a key question: "Is it possible to measure the impact of sporting properties and events in a holistic, conservative, and reliable way?" This research endeavors to build on the academic literature to add to the scope and rigor of economic impact research by proposing an impact assessment process model for practitioners that facilitates employment of a holistic, conservative and reliable impact study and seeks to address these concerns. Design/methodology/approach: Using seven identified key realities that highlight the challenges facing impact studies, and adopting a collaborative self-ethnographic methodological approach, the work highlights lessons learned from four empirical economic impact studies undertaken by the authors over a five-year period. Findings: The study provides a broad view of impact studies, which extend beyond financial implications and provides a more inclusive methodology. Particularly, the proposed impact assessment process model seeks to improve the credibility of impact studies by facilitating a holistic approach that incorporates direct, indirect and intangible impacts. Research limitations/implications: The proposed model has value to researchers and is designed to improve the overall credibility of economic impact methodology. It also provides a more accurate measure of direct impact while considering intangible and indirect impacts, including social/community impacts. Practical implications: The proposed model has value to and practitioners and is designed to improve the overall credibility of economic impact methodology. It also provides a more accurate measure of direct impact while considering intangible and indirect impacts, including social/community impacts. Originality/value: The proposed process model to measure the impact of a sports event is a needed element in the world of funding, managing and implementing events of all sizes.